Effect and mechanism of Vav3 gene to regulate inhibitor of apoptosis proteins in human gastri cancer cell line BGC823 - Bi-bo Tan; Yu Liu; Dong Wang; Qun Zhao; Li-qiao Fan; Yong Li (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: The purpose of this study is to examine expression of Vav3 and effect and mechanism of Vav3 gene to regulate inhibitor of apoptosis proteins in human gastri cancer cell line BGC823 is also explored. Methods: The expression of Vav3 in gastric cancer tissues and cell lines were detected. Specific siRNA targeting Vav3 were designed, synthesized, and transfected into BGC823. The expression of Vav3 was detected by real-time quantitative PCR and western blot Cytoactive was measured with MTT assay Cell apoptosis rate were determined by flow cytometry (FCM). The expressions of Survivin, c-IAP1, c-IAP2, XIAP, Livin and Caspase-3 were also determined. Results: Vav3 was significantly up-regulated in gastric cancer tissues and gastric cancer cell line (both P<0.01). Cell activity of BGC823 was inhibited after Vav3- siRNA was transfected into BGC823 (P<0.05). The apoptosis rate was higher after Vav3-siRNA transfected into BGC823 (P<0.05). The expressions of Survivin, c-IAP1, c-IAP2, XIAP were lower in BGC823 after Vav3-siRNA tansfected (both P0.05), and no obviously change was found in Livin (P<0.05). Conclusion: Vav3 gene silencing effectively promoted gastric cancer cell apoptosis.